Misdemeanor arrestees with mental health needs: diversion and outpatient services as a recidivism reduction strategy - Alarid, Leanne Fiftal (International journal of offender therapy and comparative criminology, 2018)
Individuals with mental illnesses who are arrested for criminal activity cycle between criminal justice and mental health systems at disproportionately high rates. Studying recidivism of this population has been difficult due to separate system data bases. This study compared recidivism outcomes of 102 adults with mental illness who were arrested for a misdemeanor offense. One group had a diagnosed mental illness (n = 58) and the other group was diagnosed with co-occurring mental health and substance abuse disorders (n = 44). As a condition of their personal recognizance bond, both groups voluntarily agreed to stabilize on medication and report to community-based outpatient mental health clinic. Participants in both groups had fewer rearrests and fewer days in jail in the 12 months following discharge from diversion relative to the 12 months prior to diversion participation. Outpatient mental health service utilization following 24 hr in jail seems to be a viable means of reducing recidivism among accused misdemeanant defendants.